Gelam Honey: a review of its antioxidant, anti-inflammatory, anticancer and wound healing aspects - Putri Shuhaili S,; Haszianaliza H,; Muhammad Fairuz A,; Zar, Chi Thent (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
In recent years, there is a growing enthusiasm in honey which has potential health benefits, disease prevention and serves as substitution of modern medicine. Honey is a natural sweet product which is produced by honey bees from floral nectar and has been traditionally used to treat several diseases such as cardiovascular disease, diabetes mellitus, cancer and Alzheimer’s disease since ancient times. Gelam honey (GH) is one of the Malaysian wild monofloral honey which is widely used as traditional medicine by the local population. GH is enriched with several therapeutic properties namely, antioxidative, antiinflammatory, anticancer and accelerated wound healing activities. However, there is lack of literature focusing on the overall effects of GH and its medicinal value. This review paper summarises the phytochemistry characteristics of GH along with its therapeutic values which lead to a broad spectrum idea on several diseases. A concise clarification on the therapeutic properties of GH is expected to provide new knowledge to the scientific society in the era of modern globalization.